Respuesta :
Answer:
Option C. y= ( -x)^2 -4
Step-by-step explanation:
If we have a function [tex]f(x) = ax ^ 2[/tex] and we want to transform it into a function g(x) that is equal to f(x) displaced c units down on the y-axis, then we must do:
[tex]g(x) = f(x) -c[/tex]
In this case we want to move the function 4 units down, then:
[tex]g(x) = f(x) -4\\\\g(x) = x ^ 2 -4[/tex]
Finally, to reflect the function on the y-axis. must do [tex]y = g(-x)[/tex]
Then we have the following function:
[tex]g(-x) = (-x) ^ 2 -4\\\\y = (-x) ^ 2 -4[/tex]
The answer is option C